Burnout and Long-term Sickness Absence From the Teaching Function: A Cohort Study - Denise A.J. Salvagioni; Arthur E. Mesas; Francine N. Melanda; Alberto D. González; Selma M. de Andrade (Elsevier, 2022)
Background: The present objective was to verify whether burnout (emotional exhaustion [EE], depersonalization [DP] and low professional efficacy [PE]) is a risk factor for long-term sickness absence (LTSA; ≥30 consecutive days) from the teaching role. Methods: This was a prospective cohort study with two years of follow-up that investigated 509 elementary and high-school teachers. Burnout was identified by Maslach Burnout Inventory. Poisson regression with robust variance was used to adjust for possible confounders. Results: The incidence of LTSA was 9.4%. High EE levels were associated with LTSA in the crude analysis, but the association lost statistical significance after adjustments (for sex, age, perception of work-life balance, general self-rated health, chronic pain and depression). High DP levels were associated with this outcome, even after all adjustments (relative risk = 1.80; 95% confidence interval: 1.05-3.09). Low PE levels were not related to LTSA. Conclusion: The results reinforce the need to improve teachers' work conditions to reduce burnout, particularly DP, and its consequences.